Expansins in the bryophyte Physcomitrella patens - Schipper, Ori; Schaefer, Didier G.; Reski, Ralf; Fleming, Andrew (My University, 2002)
Expansins are cell wall proteins which play a key function in basic processes of plant growth and differentiation. It has been proposed that expansins are likely to be present in all land plants and, to date, they have been reported in angiosperms, gymnosperms and pteridophytes. In this paper, we provide the first report and analysis of genes encoding expansin-like proteins in the bryophyte, Physcomitrella patens. Our analysis indicates that both α- and β-expansins are present as gene families in this plant and expression analysis indicates that these genes are subject to a complex regulation by both hormonal and environmental factors. In particular, the expression of many expansin genes in P. patens is upregulated by stress conditions, suggesting that they play a role in the specific cellular differentiation displayed by P. patens in response to such stress. Finally, we provide the first report on the generation and analysis of a series of knockout mutants for individual expansin genes.
Keywords: abiotic stress; auxin; expansin; gene targeting; Physcomitrella patens